FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN IBU RUMAH TANGGA TENTANG DAGING SAPI YANG AMAN, SEHAT, UTUH DAN HALAL (ASUH) DI KECAMATAN ALAM BARAJO KOTA JAMBI - M. Randa Fahsya; Nahri Idris; Indra Sulaksana (PT. Hasba Edukasi Mandiri, 2025)
The lack of knowledge of housewives about selecting safe, healthy, whole, and halal (ASUH) meat makes unscrupulous traders take the opportunity to commit fraud. The ASUH concept emphasizes that beef must be free from dangerous contaminants (safe), have beneficial nutritional content (healthy), not mixed with other parts or other animals (whole), and processed according to Islamic law (halal). This study aims to determine the knowledge of housewives about Safe, Healthy, Whole, and Halal (ASUH) beef and analyze the influence of age, education, number of family members, income, and opportunity to obtain information on knowledge about ASUH beef. The research method used is a survey with a quantitative approach. The results of this study indicate that the knowledge of housewives in Alam Barajo District is categorized as high, this can be seen from the majority of housewives knowing about ASUH beef. The conclusion of this study is that the majority of housewives in Alam Barajo District have a good understanding of the concept of ASUH beef. Income factors and opportunities to obtain information influence knowledge about ASUH beef.